A fully yarn integrated tag for tracking the international textile supply chain. (July 2016) - Kumar, Vijay; Koehl, Ludovic; Zeng, Xianyi
Highlights: This research presents the idea of fully integrated tracking tags for textile supply chain. A new optical features based yarn coding scheme has been introduced. A decision support system has been developed to characterize coded yarns. Wrapped yarns qualify the criteria to use as traceability markers in textiles. Abstract: Textile and clothing industry is one of the classical manufacturing industries which have recently undergone major transformations due to delocalization and high market volatility. In this context, one solution to guarantee the control and optimization of globalized supply chain is the implementation of a traceability system to follow-up the activities of different actors of the supply chain, improve brand value by countering pirate and enhance value creation in reverse supply chain. Therefore, in this paper, we first introduce the idea of fully integrated tracking tags for casting traceability in the textile. Then, as one stage of the traceability system development, we describe a yarn coding scheme to transform a textile structure into a tracking tag. Here, a number of special yarns were coded according to various combinations of optical characteristics. Further, a recognition system was developed for identifying the unique identification yarn code by using different image analysis techniques.